Pengenalan Budaya Keselamatan dan Kesehatan Kerja di Laboratorium Sekolah Menengah Atas melalui Edukasi - Nurwadia Sri Putri Rahmadani; Andi Yepita Deviyanti; Cici Chairunisa Mas'um; Hardianty Hardianty; Siti Nurmanis Sari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
School laboratories are learning environments that have high potential hazards, both from exposure to chemicals, the use of complex equipment, and other environmental factors. Unfortunately, the application of occupational safety and health (K3) principles in schools is still often ignored, increasing the risk of accidents and occupational diseases. In response to this issue, the S1 Occupational Safety and Health Study Program of the Batari Toja Bone Institute carried out Community Service (PKM) activities which aimed to increase students' understanding of the importance of K3 culture in the laboratory. This activity was held on August 13, 2025 at SMAN 3 Bone by involving students of class XII.F.3 as the main participants. The method of implementing the activity includes filling out an initial questionnaire to measure the level of initial understanding of students, delivering material through lectures and direct demonstrations, and interactive question and answer sessions to deepen participants' understanding. The material presented included identification of potential hazards in the laboratory, procedures for using personal protective equipment (PPE), recognition of K3 signs, and strategies to prevent the risk of work accidents. The results of the evaluation showed a significant increase in students' understanding of aspects of K3, which was shown through the comparison of questionnaire results before and after the activity. Students become more aware of the importance of using PPE, are able to recognize K3 signs, and understand preventive measures in dealing with potential dangers in the laboratory. This activity is expected to encourage the formation of a K3 culture in the school environment, so as to create a safe, healthy, and productive learning atmosphere. In addition, this program is an educational model that can be replicated in other schools as a preventive effort in managing work risks in the educational environment.